(untitled) (Research, Society and Development, 2025)
Objective: To detail the correct dental treatment for patients receiving antiplatelet therapy during dental extractions, examining the scientific literature in order to define protocols and hemostatic actions that reduce the risks of bleeding and thromboembolic events. Methodology: A rigorous analysis of the literature on surgical treatment in patients receiving antiplatelet therapy was carried out, examining research published in recent years. The most frequently used protocols, clinical strategies for discontinuing or maintaining medication, and hemostatic techniques used were analyzed. Results: The findings highlight two fundamental strategies: discontinuation and persistence of antiplatelet therapy. The research indicates that discontinuing treatment may decrease the danger of bleeding, however, it considerably increases the danger of thromboembolic events, such as myocardial infarction or stroke. On the other hand, maintaining antiplatelet therapy, in combination with local hemostatic measures such as sutures, tranexamic acid, and collagen sponges, facilitates efficient management of postoperative bleeding, with no notable differences relative to patients who discontinue treatment. Conclusions: It is common to maintain antiplatelet therapy during minor dental interventions, such as extractions, provided the correct hemostatic measures are used. This method reduces thromboembolic hazards and facilitates effective bleeding control.